PADANGBULIA PEOPLE'S RESISTANCE TO PUBLIC POLICY NUMBER 10 OF 1951 CONCERNING THE ABOLITION OF THE MANAK SALAH TRADITION - Suraya, Rahmat Sewa; Rustiani, Komang Wahyu; Suardika, I Ketut (STMIK Widya Cipta Dharma, 2024)
In Bali, the birth of